Quantitative determination of cytotoxic friedo-nor-oleanane derivatives from five morphological types of Maytenus ilicifolia (Celastraceae) by reverse-phase high-performance liquid chromatography - Buffa, W.; Corsino, J.; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Pereira, AMS; Franca, S. C. (Wiley-Blackwell, 2002)
Five different morphological types of Maytenus ilicifolia of the same age and harvested under the same conditions showed distinct accumulations of some friedo-nor-oleananes. A rapid, sensitive and reliable reverse-phase HPLC method (employing an external standard) was used for the determination of the cytotoxic triterpenoids, 20alpha-hydroxymaytenin, 22beta-hydroxymaytenin, maytenin, celastrol and pristimerin in each of the five types. Well resolved peaks with good detection response and linearity in the range 1.0-100 mug/mL were obtained. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: reverse-phase high-performance liquid chromatography; quantitative determination; friedo-nor-oleanane derivatives; root bark; Maytenus ilicifolia; Celastraceae; morphological types